Can air pollution affect tear film stability? a cross-sectional study in the aftermath of an explosion accident - Granslo JT; Magerøy N; Bakke JV; Wieslander G; Norbäck D; Moen Bente E; Irgens Å; Bråtveit M; Hollund BE; Aasen T (BMC, 2011)
Abstract Background After an explosion and fire in two tanks containing contaminated oil and sulphur products in a Norwegian industrial harbour in 2007, the surrounding area was polluted. This caused an intense smell, lasting until the waste was removed two years later. The present study reports examinations of tear film break up time among the population. The examinations were carried out because many of the people in the area complained of sore eyes. The purpose of the study was to assess the relationship between living or working close to the polluted area and tear film stability one and a half years after the explosion. Methods All persons working or living in an area less than six kilometres from the explosion site were invited to take part in the study together with a similar number of persons matched for age and gender living more than 20 kilometres away. Three groups were established: workers in the explosion area and inhabitants near the explosion area (but not working there) were considered to have been exposed, and inhabitants far away (who did not work in the explosion area) were considered to be unexposed. A total of 734 people were examined, and the response rate was 76 percent. Tear film stability was studied by assessing non-invasive break-up time (NIBUT) using ocular microscopy. In addition Self-reported Break Up Time (SBUT) was assessed by recording the time the subject could keep his or hers eyes open without blinking when watching a fixed point on a wall. Background information was obtained using a questionnaire. Non-parametric Wilcoxon-Mann-Whitney-tests with exact p-values and multiple logistic regression analyses were performed. Results Both NIBUT and SBUT were shorter among the male exposed workers than among the inhabitants both near and far away from the explosion area. This was also found for SBUT among males in a multiple logistic regression analysis, adjusting for age and smoking. Conclusions Reduced tear film stability was found among workers in an area where an explosion accident had occurred.